2014
DOI: 10.3109/09637486.2013.854747
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying rate, glycemic and appetite response to a liquid meal in lean and overweight males

Abstract: The effect of body weight status on appetite, glycemic response and gastric emptying rate was investigated using a liquid meal. Lean and overweight males rated their subjective appetite with blood samples collected for measurement of glucose, biomarkers of appetite and gastric emptying rate for 3 h following consumption of the isocaloric test meal. Overweight participants had a higher rating on postprandial hunger (p < 0.001), preoccupation with food (p < 0.001) and desire to eat (p < 0.001), with fullness bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The potential role of phenotypic or individual variability on GI peptides profile and satiety responses has been presented in previous reviews [14,82,92]. Hence, finally, since our current review targeted only a healthy, lean adult population, our findings are not applicable to obese populations which may have a unique GI peptides profile, although notable this is not without conflicting results [53]. Clamp and colleagues [57] recently demonstrated that obese individuals who habitually consume a high-fat diet had a lower postprandial PYY response than lean individuals, yet similar ad libitum energy intake between the two groups.…”
Section: Discussionmentioning
confidence: 94%
“…The potential role of phenotypic or individual variability on GI peptides profile and satiety responses has been presented in previous reviews [14,82,92]. Hence, finally, since our current review targeted only a healthy, lean adult population, our findings are not applicable to obese populations which may have a unique GI peptides profile, although notable this is not without conflicting results [53]. Clamp and colleagues [57] recently demonstrated that obese individuals who habitually consume a high-fat diet had a lower postprandial PYY response than lean individuals, yet similar ad libitum energy intake between the two groups.…”
Section: Discussionmentioning
confidence: 94%
“…Satiation is the ‘process that leads to the termination of eating; therefore controls meal size’, while satiety is the ‘process that leads to inhibition of further eating, decline in hunger, increase in fullness after a meal has finished’. It should be noted that for logistical reasons most studies of satiety do not generally measure the length of the inter-meal interval but measure appetite sensations or biomarkers of appetite over a fixed period (typically 3–4 h) (for example, Zhu et al ( 38 , 39 ) and Emilien et al ( 40 ) ). After this period, food intake at a test meal is measured and used as a marker of satiety ( 37 ) .…”
Section: Terminologymentioning
confidence: 99%
“…Typically, release of gastric contents occurs over a period from some minutes after consumption until up to 6 h or more, but with the main peak of release of stomach contents after 1.5–2 h . Rates of gastric emptying have been reported to be faster in overweight individuals . A recent meta study of 20 published trials identified that exercise intensity, mode, duration and the nature of meal/fluid ingested all influence variation in gastric emptying results during and after acute exercise .…”
Section: Human Digestion – An Overview Of the Processmentioning
confidence: 99%